2004
DOI: 10.1086/386540
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metallicity on Cepheid‐based Distances

Abstract: We have used the Wide Field Planetary Camera 2 on board the Hubble Space Telescope to obtain V and I images of seven nearby galaxies. For each, we have measured a distance using the tip of the red giant branch (TRGB) method. By comparing the TRGB distances with published Cepheid distances, we investigate the metallicity dependence of the Cepheid period-luminosity relation. Our sample is supplemented by 10 additional galaxies for which both TRGB and Cepheid distances are available in the literature, thus provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
319
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(360 citation statements)
references
References 86 publications
32
319
9
Order By: Relevance
“…It is close to the large spiral galaxy M83 in projection. However the distance to M83, 4.8 Mpc 39 , is significantly larger than the distance to NGC 5253, at 3.8 Mpc 40 . The HI streamer system 24,25 in the halo of NGC 5253 from which the CO streamer appears to emanate strongly suggests that this dwarf galaxy has had some encounter in its past, but M83 does not appear to be responsible.…”
Section: Methodsmentioning
confidence: 72%
“…It is close to the large spiral galaxy M83 in projection. However the distance to M83, 4.8 Mpc 39 , is significantly larger than the distance to NGC 5253, at 3.8 Mpc 40 . The HI streamer system 24,25 in the halo of NGC 5253 from which the CO streamer appears to emanate strongly suggests that this dwarf galaxy has had some encounter in its past, but M83 does not appear to be responsible.…”
Section: Methodsmentioning
confidence: 72%
“…The calibration of the TRGB magnitude M * I is very solid. Sakai et al (2004) found M * I = −4.05 mag from globular clusters. Rizzi et al (2007) fitted the horizontal branch (HB) of five galaxies to a metal-corrected HB from Hipparcos parallaxes and obtained the same value.…”
Section: The Tip Of the Red-giant Branch (Trgb) As A Distance Indicatormentioning
confidence: 98%
“…The CMD of the entire WFPC2 field, reaching deeper into the disc population, is swamped with an admixture of evolved AGB stars and supergiants such that the TRGB becomes invisible to the eye and also the edge detection spectrum becomes much noisier (Fig.1 right). Rizzi et al (2007) have remeasured the field of Sakai et al (2004) and found m * I = 25.29 ± 0.08. The mean of m * I = 25.35 ± 0.05 is adopted here.…”
Section: The Trgb In Mixed Populationsmentioning
confidence: 99%
“…With m corr V = 8.92 ± 0.16 and a TRGB distance of (m − M) = 28.21 (Sakai et al 2004;Rizzi et al 2007 …”
Section: The Sn 1937c In Ic 4182mentioning
confidence: 99%